Global Pattern of CD8+ T-Cell Infiltration and Exhaustion in Colorectal Cancer Predicts Cancer Immunotherapy Response - Tian, Sun; Wang, Fulong; Zhang, Rongxin; Chen, Gong (Frontiers in Pharmacology, 2021)
Background: MSI/MSS status does not fully explain cancer immunotherapy response in colorectal cancer, we develop a colorectal cancer specific method that predicts cancer immunotherapy response. Methods: We used gene expression data of 454 samples (MSI=131, MSI-L=23, MSS=284, Unknown=16) and developed a method TMEPRE that models signatures of CD8+ T cell infiltration and CD8+ T cell exhaustion states in the tumor microenvironment of colorectal cancer. TMEPRE model was validated on three RNAseq datasets of patients who received pembrolizumab or nivolumab and one RNAseq dataset of purified CD8+ T cells in different exhaustion states. Results: TMEPRE showed predictive power in three datasets of anti-PD1 treated patients(p=0.056, 0.115, 0.003). CD8+ T cell exhaustion component of TMEPRE model correlates with anti-PD1 responding progenitor exhausted CD8+ T cells in both tumor and viral infection(p=0.048, 0.001). Global pattern of TMEPRE on 454 colorectal cancer samples indicated that 10.6% of MSS patients and 67.2% of MSI patients show biological characters that can potentially benefit from anti-PD1 treatment. Within MSI nonresponders, approximately 50% showed no sufficient amount of tumor infiltrating CD8+ T cells and 50% showed terminal exhaustion of CD8+ T cells. These terminally exhausted CD8+ T cells coexisted with signatures of myeloid-derived suppressor cells in colorectal cancer. Conclusion: TMEPRE is a colorectal cancer specific method. It captures characters of CD8+ T cell infiltration and CD8+ T cell exhaustion state, and predict cancer immunotherapy response. A subset of MSS patients could potentially benefit from anti-PD1 treatment. Anti-PD1 resistance MSI patients with insufficient infiltration of CD8+ T cell or terminal exhaustion of CD8+ T cells need different treatment strategies.